2011
DOI: 10.1186/1743-422x-8-456
|View full text |Cite
|
Sign up to set email alerts
|

Human platelets express CAR with localization at the sites of intercellular interaction

Abstract: Adenovirus has a wide tissue tropism. The virus attaches to the surface of cells via the fiber protein knob binding to the Coxsackie and Adenovirus receptor known as CAR. Virus entry inside cells is facilitated by integrins αVβ3 and αVβ5. Mice platelets are shown to be the predominant Ad binding blood cell type and the virus is documented inside platelets. CAR was identified on human platelets in one study yet contradicted in another. The presence of CAR appears to be the most reasonable initial step for virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 8 publications
0
28
0
Order By: Relevance
“…While treatment with the anti‐CAR blocking Ab significantly reduced (> 2 logs) the titers in Vero cells, viral titers associated with platelet supernatants or pellets were not changed following preincubation with the anti‐CAR Ab, strongly suggesting that the association between CVB and platelets was CAR‐independent. Of note, the presence of CAR on the platelet surface is still controversial, because it has been shown to be absent , present in all platelets or restricted to a sub‐fraction (3%) of the platelets . Although some CVB interact with the decay‐accelerating factor (DAF) , which is a complement regulatory protein that is expressed commonly on most cell surfaces, including human platelets , our previous studies showing that the CVB3 variant used was not blocked by soluble recombinant human DAF or by blocking antisera, as reported by others , strongly suggest that DAF was not involved.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…While treatment with the anti‐CAR blocking Ab significantly reduced (> 2 logs) the titers in Vero cells, viral titers associated with platelet supernatants or pellets were not changed following preincubation with the anti‐CAR Ab, strongly suggesting that the association between CVB and platelets was CAR‐independent. Of note, the presence of CAR on the platelet surface is still controversial, because it has been shown to be absent , present in all platelets or restricted to a sub‐fraction (3%) of the platelets . Although some CVB interact with the decay‐accelerating factor (DAF) , which is a complement regulatory protein that is expressed commonly on most cell surfaces, including human platelets , our previous studies showing that the CVB3 variant used was not blocked by soluble recombinant human DAF or by blocking antisera, as reported by others , strongly suggest that DAF was not involved.…”
Section: Discussionmentioning
confidence: 92%
“…Hemorrhage and/or impaired platelet functionality are not associated with CVB human infections. However, these viruses are interesting for the study of platelet‐virus interaction because their specific Coxsackie‐Adeno receptor (CAR) expression was described on platelets , CVB3 infection in mice resembles human infection , and the murine model has been extensively used in pathogenesis studies . Therefore, to further understand the role of platelets during viral pathogenesis, in the present study we analyzed in vitro and in vivo CVB interaction with platelets and found that platelets play a critical role in host survival and immune response against CVB3 infection.…”
Section: Introductionmentioning
confidence: 91%
“…Studies have shown that after intravenous Ad5 administration, the virus can bind to circulating CAR-expressing platelets, causing their activation and degranulation [17] . Platelets were counted after 6 h of incubation with clinical-grade AdVince in human blood using the blood loop model.…”
Section: Safety Assessment Of Clinical-grade Advince In Human Bloodmentioning
confidence: 99%
“…These include: triggering systemic inflammation and clearance of activated platelets via splenic/liver macrophages and/or phagocytosis by neutrophils such as the case in influenza and rhinoviruses,5 suppressing platelet production or enhancing platelet destruction such as the case in herpes and simian viruses,5 and anti-viral antibodies cross-reacting with platelet surface integrins such as the case in adenovirus (platelet integrin GPIIb/IIIa) 5,7. Platelets were found to express the Coxsackie adenovirus receptor (CAR); in-vitro and in-vivo studies showed direct adenovirus-platelet interactions, followed by platelet activation as evidenced by increased expression of P-selectin with subsequent formation of platelet-leukocyte aggregates and expression of leukocytes and endothelial cells' activation markers 8,9. Furthermore, the adenovirus-induced thrombocytopenia was found to be dependent on von Willebrand factor (VWF) sinceManuscript handled by: James Morrissey Final decision: James Morrissey, 06 April 2020 VWF-knockout (KO) mice did not show thrombocytopenia when injected by the virus.…”
mentioning
confidence: 99%